The HIV cascade of care and service utilisation at sex work programmes mong female sex workers in South Africa - Jaffer, Maya (My University, 2021)
Introduction: Female sex workers (FSWs) in South Africa experience uniquely high prevalence of HIV. There are multiple barriers to FSWs accessing HIV testing and treatment services, including the effects of stigma on health-seeking behaviour. It is well-established that engagement with HIV services is improved in the setting of a sex worker friendly programme. Therefore, National Department of Health (NDoH) has scaled-up specialised programmes to provide HIV services through the implementation of the National Sex Work HIV Plan 2016-2019, with the aim of reaching the 90:90:90 cascade of care (CoC) goals. This study aimed to describe the current CoC in FSWs in South Africa, and explore the impact on service use at these sex work programmes on this CoC. Methodology: The primary study was a cross-sectional national study, that collected survey and laboratory data from FSWs in all nine provinces of South Africa, from February – July 2019. This secondary analysis considered all 1862 participants with HIV in this study. New variables were created to describe the HIV CoC with respect to known positivity, current antiretroviral treatment (ART) and viral suppression. A multivariable regression model assessed factors associated with successful viral suppression, including sex work programme service use variables. Results: 1862 FSWs with HIV were enrolled. 92% (1708/1862) were known HIV positive, and 87% (1453/1673) of these currently on antiretroviral treatment (ART). Of those on ART, 74% (1024/1385) were virally suppressed. Age was strongly associated with the CoC, with younger FSWs less likely to be on ART or virally suppressed (p<0.001). FSWs using HIV services from specialised programmes were 1.4 times more likely to be virally suppressed (95% CI: 1.1 – 1.9, p=0.012) than those not. Conclusions: The HIV CoC in FSWs in South Africa is high, with marked improvement from previous estimates, prior to the implementation of the National Sex Work HIV Plan 2016-2019. Known positivity and current ART treatment effectively reach 90:90:90 goals, though viral suppression lags significantly behind. The findings affirm the work of sex work programmes, with the use of HIV services from these programmes improving the odds of viral suppression in the multivariable regression model. Further attention needs to be paid to the poorer CoC outcomes in younger FSWs, who are less likely to be on ART or virally suppressed.
A research report submitted to the School of Public Health, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master’s in Public Health, 2021